2014
DOI: 10.1007/s12529-014-9441-3
|View full text |Cite
|
Sign up to set email alerts
|

Skin Tone Dissatisfaction, Sun Exposure, and Sun Protection in Australian Adolescents

Abstract: Skin tone dissatisfaction plays an important role in Australian adolescents' sun-related behavior. Appearance-based interventions may be effective in reducing skin cancer risk through reduced sun exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…We found in our study that the rate of using SPPs with a SPF less than 15 was 3.3% and those with a SPF over 30 was 60.2%, which may be attributed to the fact that people started to perceive in recent years that as the factor level increased, the effectiveness of the product in protection from the sun also increased and for this reason, people tend to use sun creams with higher factors. Compatible with studies by Hutchinson et al 18 (44%) and FernandezMorano et al 19 (47.8%), 44.3% of subjects included in our study used SPPs. In their study carried out in Australia, Pruim et al 20 reported that 61% of subjects had repeated application of SPPs.…”
supporting
confidence: 74%
“…We found in our study that the rate of using SPPs with a SPF less than 15 was 3.3% and those with a SPF over 30 was 60.2%, which may be attributed to the fact that people started to perceive in recent years that as the factor level increased, the effectiveness of the product in protection from the sun also increased and for this reason, people tend to use sun creams with higher factors. Compatible with studies by Hutchinson et al 18 (44%) and FernandezMorano et al 19 (47.8%), 44.3% of subjects included in our study used SPPs. In their study carried out in Australia, Pruim et al 20 reported that 61% of subjects had repeated application of SPPs.…”
supporting
confidence: 74%
“…As long as the standards of healthfulness and beauty remain unaltered, efficacious prevention initiatives will be severely limited. 18,22 Taking together, these findings have important clinical implications.…”
Section: Discussionmentioning
confidence: 93%
“…More than 90% of participants pointed to the importance of applying sunscreen in order to prevent negative consequences of sun exposure, even though it could slow down or reduce desired tan. Nevertheless, this might be the result of misinterpreted interventions more focused on sunscreen use than on appearance motivations or social desirability of being tan, used by students to tan “safely.” As long as the standards of healthfulness and beauty remain unaltered, efficacious prevention initiatives will be severely limited …”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that both adolescents (Hutchinson, Prichard, Ettridge, & Wilson, 2015) and young adults are dissatisfied with their skin tone (Prichard, Kneebone, Hutchinson, & Wilson, 2013) and are frequent users of SNSs (Pew Research Center, 2018a, 2018b). Although differences in sun behaviors between adolescents and young adults have been assessed (Dobbinson et al, 2008), these differences have not been investigated in relation to SNS activities.…”
mentioning
confidence: 99%